Gender Diversity and Performance in Islamic Banks: Evidence from Emerging Markets - Anam, Khoirul; Wijaya, Kusuma (Journal International Economic Sharia, 2025)
Objective: This study aims to investigate the relationship between gender diversity and financial performance in Islamic banking, focusing in particular on the moderating effect of Sharia governance.Methods:  Data about female representation on bank boards, in bank top management, gender diversity in recruitment, and an index of five Sharia Governance elements are collected. Moreover, financial performance is assessed using multiple indicators.Results:  The results of this study illustrate a strong positive correlation between bank financial performance and gender diversity at the board, executive level, and organizational level. A key aspect of this study is the finding that Sharia Governance indeed positively moderates the relationship, further improving the financial impact of gender diversity. This finding is supported through robust sensitivity analysis and variation in performance indicators. It supports further and confirms the synergic positive relationship between ethical governance and diverse leadership.Novelty: The original contribution of this study is the integration between gender diversity and Sharia theory to the emerging Sharia governance theory, going beyond traditional corporate governance models. This approach does not consider Sharia governance as an independent factor but rather as an enhancing moderator to the financial return of other factors, offering a new and ethically valid perspective to the business case on faith-based institutions’ inclusion.Research Implication: In practical terms, this encourages regulators and Islamic finance councils to prioritize Shariah governance and gender inclusion, both as strategic drivers of sustainable performance and ethical compliance across the global industry